Visual outcomes and corneal changes after intrastromal femtosecond laser correction of presbyopia - Menassa, Nardine; Fitting, Anna; Auffarth, Gerd U.; Holzer, Mike P. (Journal of cataract and refractive surgery, 2012)
Purpose: To assess the effect of intrastromal femtosecond laser presbyopia treatment on uncorrected near visual acuity (UNVA) and corneal integrity over an 18-month period. Setting: Department of Ophthalmology, International Vision Correction Research Centre, University of Heidelberg, Heidelberg, Germany. Design: Clinical trial. Methods: The UNVA (at 40 cm), corneal pachymetry, and true net power were evaluated preoperatively and 1, 3, 6, 12, and 18 months after femtosecond intrastromal presbyopic treatment (Intracor). Endothelial cell density (ECD) was measured preoperatively and 3, 6, and 12 months postoperatively. Data were analyzed with the Wilcoxon test at a P=.01 level of significance. Results: The median UNVA improved significantly from 0.7 logMAR preoperatively to 0.4 logMAR, 0.2 logMAR, 0.2 logMAR, 0.3 logMAR, and 0.2 logMAR at 1, 3, 6, 12, and 18 months, respectively (all P<.001). The median corneal true net power increased significantly by 1.1 diopters (D) to 0.7 D, 0.8 D, 1.0 D, and 0.9 D, respectively (all P<.001); pachymetry showed no significant thinning postoperatively. There was no significant difference in ECD between preoperatively and postoperatively. Conclusions: Intrastromal femtosecond presbyopic treatment yielded a significant and stable gain of UNVA and corneal steepening without significant loss of endothelial cells or corneal thinning up to 18 months postoperatively. No significant regression of visual acuity or further corneal steepening occurred during the follow-up period. Financial Disclosure: Dr. Auffarth and Dr. Holzer received lecture and consulting fees from Technolas Perfect Vision GmbH. No author has a financial or proprietary interest in any material or method mentioned.
Gesehen am 28.11.2018